The Role of Gender in the Influence of Love of Money and Tax Understanding on Ethical Perceptions of Tax Evasion - Sa'dani, Olivi Sabilla; Aisa, Nabila Na'ma; Izwan, Iylia Dayana Mohamed (Reviu Akuntansi dan Bisnis Indonesia, 2025)
Background: Tax revenue in Indonesia has continued to increase annually, along with the number of tax dispute cases. Tax disputes that frequently occur in Indonesia are largely caused by tax evasion. Tax evasion is closely related to ethics, as judgments about its ethicality are based on moral considerations.Purpose: This study aims to examine the role of gender in the influence of love of money and tax understanding on ethical perceptions of tax evasion.Methodology: The sampling method employed was incidental sampling, yielding 102 respondents consisting of individual taxpayers in the Special Region of Yogyakarta. Data were analyzed using Moderation Partial Least Squares–Structural Equation Modeling (PLS-SEM).Research findings: The findings indicate that love of money has a positive and significant effect on ethical perceptions of tax evasion, while tax understanding does not affect ethical perceptions of tax evasion. Gender does not moderate the effect of either love of money or tax understanding on ethical perceptions of tax evasion.Originality/Theoretical contribution: This study integrates the Theory of Planned Behavior and Gender Socialization Theory to explain factors influencing ethical perceptions of tax evasion. It provides new insights into how affective and cognitive dimensions shape ethical views on tax evasion and how gender functions as a moderating variable among individual taxpayers in the Special Region of Yogyakarta, known for its srawung (communal social interaction) culture.